2015
DOI: 10.1007/s12012-015-9314-2
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz Causes Oxidative Stress, Endoplasmic Reticulum Stress, and Autophagy in Endothelial Cells

Abstract: The non-nucleoside reverse transcriptase inhibitor efavirenz is a widely prescribed antiretroviral drug used in combined antiretroviral therapy. Despite being an essential and life-saving medication, the required lifelong use of HIV drugs has been associated with a variety of adverse effects, including disturbances in lipid metabolism and increased cardiovascular risk. Efavirenz belongs to those HIV drugs for which cardiovascular and endothelial dysfunctions have been reported. It is here shown that elevated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 25 publications
4
29
0
Order By: Relevance
“…We have previously described a complex effect of the antiretroviral drug efavirenz, a member of the non‐nucleoside analogue reverse transcriptase inhibitor family, on human hepatic cells in culture, manifested in both mitochondrial dysfunction – diminished O 2 consumption, decreased mitochondrial membrane potential (ΔΨ m ) and increased mitochondrial ROS generation (Apostolova et al, ) and the presence of ER stress with activation of the three arms of the unfolded protein response (UPR) (Apostolova et al, ). In line with evidence obtained in other cellular models (Dong et al, ; Weiß et al, ), we have shown that under these conditions, efavirenz also up‐regulates autophagy, and autophagic flux is normal at moderate efavirenz concentrations (10 and 25 μM) (Apostolova et al, ). Higher concentrations of efavirenz (50 μM) were associated with inhibited autophagic flux and induction of apoptosis (Apostolova et al, ; Apostolova et al, ).…”
Section: Introductionsupporting
confidence: 91%
“…We have previously described a complex effect of the antiretroviral drug efavirenz, a member of the non‐nucleoside analogue reverse transcriptase inhibitor family, on human hepatic cells in culture, manifested in both mitochondrial dysfunction – diminished O 2 consumption, decreased mitochondrial membrane potential (ΔΨ m ) and increased mitochondrial ROS generation (Apostolova et al, ) and the presence of ER stress with activation of the three arms of the unfolded protein response (UPR) (Apostolova et al, ). In line with evidence obtained in other cellular models (Dong et al, ; Weiß et al, ), we have shown that under these conditions, efavirenz also up‐regulates autophagy, and autophagic flux is normal at moderate efavirenz concentrations (10 and 25 μM) (Apostolova et al, ). Higher concentrations of efavirenz (50 μM) were associated with inhibited autophagic flux and induction of apoptosis (Apostolova et al, ; Apostolova et al, ).…”
Section: Introductionsupporting
confidence: 91%
“…(), in their study on obese Wistar rats, attributed the deleterious effects of HAART to increased oxidative stress. Although oxidative stress was not assessed in this study, literature is rife with reports on HAART's association with oxidative stress (Azu et al ., ; Sharma, ; Ogedengbe et al ., ; Weiß et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, investigations demonstrated that this deleterious effect was actually secondary to mitochondrial dysfunction and the release of mitochondrial calcium into the cytosol (Apostolova et al 2013). Two recent studies also showed that efavirenz-induced ER stress in human endothelial cells (Bertrand and Toborek 2015;Weiß et al 2015), but the involved mechanism was not determined in these investigations.…”
Section: Efavirenzmentioning
confidence: 97%